Preemptive one lung ventilation enhances lung collapse during thoracoscopic surgery: A randomized controlled trial. Issue 6 (21st May 2019) - Zhang, Yunxiao; Yan, Wanpu; Fan, Zhiyi; Kang, Xiaozheng; Tan, Hongyu; Fu, Hao; Li, Zhendong; Chen, Ke‐Neng; Chen, Jiheng
Abstract : In routine practice, one lung ventilation (OLV) is initiated upon pleural opening. We conducted a randomized controlled trial to compare lung collapse after preemptive OLV versus conventional OLV in thoracoscopic surgery. A total of 67 patients were enrolled (34 with conventional OLV; 33 with preemptive OLV). Preemptive OLV was conducted by closing the DLT lumen to the non‐ventilated lung immediately upon assuming the lateral position with the distal port closed to the atmosphere until pleural opening (>6 minutes in all cases). Lung collapse was assessed at 1, 5, 10, 20, 30 and 40 minutes after pleural opening using a 10‐point rating scale (10: complete collapse). The primary end point was the duration from pleural opening to satisfactory lung collapse (score of 8). Secondary end points included PaO2 and hypoxemia. The duration from pleural opening to satisfactory lung collapse was shorter in the preemptive OLV group (9.1 ± 1.2 vs. 14.1 ± 4.7 minutes, P < 0.01). PaO2 was comparable between the two groups prior to anesthetic induction (T0), and 20 (T2), 40 minutes (T3) after pleural incision, but was lower in the preemptive OLV group at zero minutes after pleural incision (T1) (457.5 ± 19.0 vs. 483.1 ± 18.1 mmHg, P < 0.01). No patients in either group developed hypoxemia. In summary, preemptive OLV expedites lung collapse during thoracoscopic surgery with minimal safety concern.